THE IMPORTANCE OF PHONETICS IN ENHANCING STUDENTS’ SPEAKING SKILLS - Marufov, Elyor (Мир исследований, 2021)
This article highlights the importance of phonetics for English speaking learners while speaking the language to a native speakers as well as understanding the context of another English speakers. The paper also emphasizes the role phonetics in improving student’s speaking skills through the result of experiments. Besides that it will be focused in part on what phonetics is and what is studied in it.